Incremental theory of personality attenuates the effect of environmental uncertainty on intertemporal choices. (November 2022) - Geng, Xiaowei; Li, Mengyue; Zhang, Feng; Li, Wenjing; Liu, Dan
To examine the impact of environmental uncertainty on individuals' intertemporal choices and the moderating effect of implicit personality theory, two studies were conducted. Study 1 investigated the moderating role of implicit personality theory in the influence of environmental uncertainty on intertemporal choice using questionnaires. Study 2 examined whether priming incremental personality theory could change entity theorists' intertemporal preference in an uncertain environment. The results showed that implicit personality theory plays a moderating role in the influence of environmental uncertainty on intertemporal choice. For entity theorists, the delay discounting rate was positively correlated with environmental uncertainty. In contrast, for incremental theorists, the delay discounting rate was not significantly correlated with environmental uncertainty. After priming incremental personality theory, entity theorists' delay discounting decreased significantly. Thus, we conclude that incremental personality theory buffers the effect of environmental uncertainty on intertemporal choice.